2014
DOI: 10.1111/jcms.12123
|View full text |Cite
|
Sign up to set email alerts
|

Overseeing Secrets in the EU: A Democratic Perspective

Abstract: Formulating policy and overseeing implementation require access to information. Yet in (national) security matters executive officials have considerable discretion to conceal from the public and from parliaments information they consider sensitive. If executive officials are given largely unchecked power to conceal from the public and from parliament(s) whatever information they consider sensitive, part of the essential machinery of democracy is disconnected. Secrecy becomes a danger when it undermines the ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…Instead, the qualitative data available suggests that leak prevention happens in selected instances, especially where the Commission leadership attempts to keep control over timing. This builds on previous research that has already shown how EU institutions try to prevent that classified EU information is published (for an overview see Curtin 2014;Galloway 2014). It also adds to recent contributions on secrecy and the "space to think" and on how they are constructed in EU institutions like the Council of the European Union and the European Council.…”
Section: The Dynamics Of Leaking In the European Commissionmentioning
confidence: 97%
See 2 more Smart Citations
“…Instead, the qualitative data available suggests that leak prevention happens in selected instances, especially where the Commission leadership attempts to keep control over timing. This builds on previous research that has already shown how EU institutions try to prevent that classified EU information is published (for an overview see Curtin 2014;Galloway 2014). It also adds to recent contributions on secrecy and the "space to think" and on how they are constructed in EU institutions like the Council of the European Union and the European Council.…”
Section: The Dynamics Of Leaking In the European Commissionmentioning
confidence: 97%
“…Where we find confidentiality enforced in Western political systems, this should be selective and limited to instances where the strategic interests of political leadership are concerned. This enriches discussions on the politics and regulation of secrecy, confidentiality, and lack of transparency in the EU (Curtin 2014;Galloway 2014;Abazi 2015;Rosén 2015;Hillebrandt and Novak 2016) and the emerging debate on secrecy in Europe.…”
Section: "By Virtue Of Their Unvarnished Nature Leaks Have Evolved Imentioning
confidence: 99%
See 1 more Smart Citation
“…This article aims to contribute to these literatures by highlighting the dynamics and significance of the practices of secrecy and publicity of the TFTP and other post 9/11 security programmes. It especially builds upon work on EU secrecy by Curtin (2014).…”
Section: Introduction: Terrorism Finance Tracking Programme Secrecymentioning
confidence: 99%
“…Information relating to national security or trade negotiating positions may be justifiable reasons to limit information flows. However, from a democratic oversight perspective, secrets should be justified and politically checkable in the broad sense that they are subordinate to policies that themselves are transparent and politically alterable (Curtin, 2014;Thompson, 1999).…”
Section: Foreign Affairs and Logics Of Secrecy And Transparencymentioning
confidence: 99%